O trabalho em plataformas digitais: uma análise do microtrabalho - Santos, Ana Carolina Gimenes dos (2021)
The present dissertation starts from the evidenced scenario with the development of the “digital economy” and the consequent changes caused in labor relations, to analyze one of the new forms of work that have emerged with digital platforms: the microtask platforms. The research intends to investigate the working conditions of the brazilians workers in microtask platforms, in addition to verify whether there are differences between the different platforms, compared to the dynamics of work at Amazon Mechanical Turk (AMT). For this purpose, besides the literature review about the crowdwork, a questionnaire was applied to 34 Brazilian workers from different microtask platforms and, subsequently, in-depth interviews were conducted with 4 of them. The exploratory nature of the study made it possible to formulate some hypotheses about microwork. Among the identified results, in general, microwork allows workers certain autonomy and flexibility of working hours, at the same time that exposes them to the risks of the absence of legal protection. On the other hand, the research allowed us to understand that there are variations in working conditions on the different platforms observed